Plant/Leaf traits and adaptive strategies of Cistus species to Mediterranean drought and insolation in southern Portugal - Fonseca, E (2014)
The effects of climate change can result in dramatic consequences in specific ecosystems such as montados that are seriously threatened by the absence of cork and holm oak (Quercus suber and Q. rotundifolia) natural regeneration. Shrubs of the genus Cistus, which are among the most important elements of encroached montados, seem to promote soil rehabilitation and enhance oak regeneration (Simões et al. 2009). In this context, we compared the life strategies and evaluated the potential ability of Cistus species to adapt to the increasing drought expected for the Mediterranean region, and thus their role on the sustainability of cork oak montados.